Comparative Efficacy of Different Tactics for the Management of Okra Shoot and Fruit Borer, Earias Vittella (Fab.) under Field Condition - Rahman, M.A.; Uddin, M.M.; Haque, M.A.; Rahman, M.M. (International Journal of Applied Sciences and Biotechnology, 2016)
Comparative field efficacy of different control measures of okra shoot and fruit borer, Earias vittella were evaluated in the Entomology Field Laboratory, Bangladesh Agricultural University during February to May, 2014. Field efficacy of two selected chemical insecticides (Decis 2.5EC, Agritaf 50SP), three botanicals (Neem oil, Pitraj oil and Mahogany oil), one parasitoid (Trichogramma chilonis), Light trap along with Hand picking and Trap crop (Maize) were evaluated by analyzing percent shoot and fruit infestations. BARI-1 (okra variety) was used as a test crop in the experiment. Among the tactics, the minimum shoot (4.72%) and fruit infestations (6.77%) were observed in the plots treated with Decis 2.5EC followed by Neem oil treated plots (4.83% in shoot and 7.56% in fruit). The highest reduction of percent shoot infestation (79.89%) and fruit infestation (64.97%) over untreated control plots was found in the Decis 2.5EC sprayed plots followed by Neem oil while the lowest percent reduction of shoot infestation (29.86%) and fruit infestation (29.43%) were recorded in case of Light trap + hand picking.  Neem oil and Decis 2.5EC were found very effective in managing E. vittella up to 7 days after each spraying. Agritaf 50SP, Pitraj oil, Mahogany oil, T. chilonis and trap crop were also found effective over untreated control plots although were significantly lower than Decis 2.5EC and Neem oil. Therefore, application of Decis 2.5EC and Neem oil were mostly effective and Light trap + hand picking was the least effective measures in controlling E. vittella.Int J Appl Sci Biotechnol, Vol 4(1): 74-78